Lower Circulating Interferon-Gamma Is a Risk Factor for Lung Fibrosis in COVID-19 Patients - Hu, Zhong-Jie; Xu, Jia; Yin, Ji-Ming; Li, Li; Hou, Wei; Zhang, Li-Li; Zhou, Zhen; Yu, Yi-Zhou; Li, Hong-Jun; Feng, Ying-Mei; Jin, Rong-Hua (Frontiers in Immunology, 2020)
SARS-CoV-2 infection and its subsequent cytokine storm are the main causes of acute respiratory distress syndrome (ARDS) and lung fibrosis. We investigate whether any inflammatory molecules could be related to lung fibrosis in COVID-19. Seventy-six COVID-19 patients admitted and recovered in Youan hospital from January 21th till March 20th 2020 were analyzed. Pulmonary fibrosis, represented as consolidation volume on chest CT images, was computed by artificial intelligence (AI)-assisted program. Plasma samples were collected shortly after admission to measure basal inflammatory molecules levels. At discharge, consolidation lesion remained in 46 (60.5%) patients whose plasma interferon-ϒ (IFN-ϒ) levels were 2-fold lower than those without fibrosis (p>0.05). Multivariate-adjusted logistic analysis demonstrated the inverse association of the risk of having lung fibrosis and basal circulating IFN-ϒ levels with estimate of 0.43 (p=0.02). Per 1-SD increase of basal IFN-ϒ level in circulation, fibrosis volume decreased by 0.070% (p=0.04) at discharge. Basal circulating IFN-ϒ levels were comparable with c-reactive protein in the discrimination of the occurrence of lung fibrosis in COVID-19 patients at discharge whereas circulating IL-6 levels could not. In conclusion, these data indicate that lower circulating IFN-ϒ is a risky factor of lung fibrosis in COVID-19.